2015
DOI: 10.1371/journal.pone.0127955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Cognitive Remediation on Cognitive Dysfunction in Partially or Fully Remitted Individuals with Bipolar Disorder: Results of a Randomised Controlled Trial

Abstract: IntroductionCognitive dysfunction is common in bipolar disorder (BD) but is not sufficiently addressed by current treatments. Cognitive remediation (CR) may improve cognitive function in schizophrenia but no randomised controlled trial has investigated this intervention in BD. The present study aimed to investigate the effects of CR on persistent cognitive dysfunction in BD.MethodPatients with BD in partial remission with cognitive complaints were randomised to 12 weeks group-based CR (n=23) or standard treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 53 publications
10
95
2
8
Order By: Relevance
“…In a recent study, 46 patients with bipolar disorder who were in full or partial remission and had subjective cognitive complaints were randomized to a 12-week cognitive rehabilitation or standard treatment (Demant, Vinberg, Kessing, & Miskowiak, 2015). While there were no group differences for the functional and main cognitive outcomes, those assigned to cognitive rehabilitation had improved subjective sharpness at week 12, and quality of life and verbal fluency at week 26 follow-up (Demant et al, 2015). A small pilot study examined the efficacy of a 10-week cognitive rehabilitation program in 33 patients with major depressive disorder who had not improved after other treatment (Bowie, Gupta, Holshausen, et al, 2013).…”
Section: Treatment Approaches Targeting Cognitive Functionsmentioning
confidence: 99%
“…In a recent study, 46 patients with bipolar disorder who were in full or partial remission and had subjective cognitive complaints were randomized to a 12-week cognitive rehabilitation or standard treatment (Demant, Vinberg, Kessing, & Miskowiak, 2015). While there were no group differences for the functional and main cognitive outcomes, those assigned to cognitive rehabilitation had improved subjective sharpness at week 12, and quality of life and verbal fluency at week 26 follow-up (Demant et al, 2015). A small pilot study examined the efficacy of a 10-week cognitive rehabilitation program in 33 patients with major depressive disorder who had not improved after other treatment (Bowie, Gupta, Holshausen, et al, 2013).…”
Section: Treatment Approaches Targeting Cognitive Functionsmentioning
confidence: 99%
“…Previously reported studies have implemented cognitive training alone or in conjunction with other symptom management and therapeutic interventions (e.g., mood management and psychoeducation) (Deckersbach et al, 2010; Preiss et al, 2013; Torrent et al, 2013; Demant et al, 2015). The cognitive training portion of these studies targeted specific processing deficits in BD, such as memory, executive function, and attention.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Deckersbach et al (2010) and Preiss et al (2013) resulted in significant cognitive and mood improvement after training, specifically with gains on measures of executive function and reductions in reported depressive symptoms. On the other hand, similarly well-constructed studies to address cognitive and psychosocial deficits in BD failed to find significant improvement in cognitive function (Torrent et al, 2013; Demant et al, 2015). While cognitive gains were not reported, the Torrent et al (2013) participants did exhibit significantly improved scores on a functional outcome measure.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent randomized trials suggest limited impact of broadly targeted cognitive remediation on objective cognitive performance in euthymic patients with BD, despite earlier open trials indicating some enhancement of cognitive ability 82,83 . Nonetheless, in the larger trial reported by Torrent involving an intervention that provided psychoeducation and behavioral practice of cognitive compensatory techniques, psychosocial functioning was enhanced to a significant degree when compared to a symptom focused psychoeducation group 82 .…”
Section: Interventions To Remediate Cognitive Impairment In Bipolar Dmentioning
confidence: 99%